Efektivitas Obat Tetes Mata Sodium Hialuronat Pada Dry Eye Disease - Grace Raveena Widelia Worumi; Jois Mauren Lumantobing; Michael Usup; Santi Anugrahsari (Fakultas Kedokteran dan Ilmu Kesehatan Ukrida, 2023)
Dry eye disease (DED) or keratoconjunctivitis sicca is a multifactorial disease of the ocular surface characterized by loss of tear film homeostasis, inflammation and damage to the ocular surface as well as neurosensory abnormalities with symptoms such as the sensation of a foreign body in the eye, dry eyes, irritation, itching and sensitivity to light, which can impact a patient's daily activities and life. The prevalence of DED is between 5% and 50% in the adult population which can be caused by factors such as female, cataract surgery, use of contact lenses, computers, thyroid disorders, hypertension, and use of antihistamines and antidepressants. One of the DED therapies is the provision of artificial tears where polymers such as hyaluronic acid can be used because they can increase tear volume and eye moisture. This literature review was made with the aim of knowing the effectiveness of sodium hyaluronate eye drops in treating dry eye disease. 8 journals were selected through the PubMed, ProQuest and Google Scholar journal databases and then presented in the form of a literature review. Based on the analysis results, sodium hyaluronate eye drops are effective in relieving dry eye symptoms.